Broken chains and subverted plans : ethnicity, race, and commodities - Fennell, Christopher (University Press of Florida, 2017)
Using two case studies from different frontier regions in 19th-century America, this work reveals how marginalised ethnic and racial communities resisted the attempts of governing officials and investors to control them through capitalist economic and government frameworks. Looking at the economic systems of these regions, Christopher Fennell offers insight into the development of America's consumer economy.